Rifaximin versus norfloxacin for prevention of spontaneous bacterial peritonitis: a systematic review. Issue 1 (17th July 2017) - Sidhu, Gurpartap S; Go, Andrew; Attar, Bashar M; Mutneja, Hemant R; Arora, Shilpa; Patel, Sanjay A
Abstract : Aim: The aim of this systematic review is to evaluate the efficacy and safety of rifaximin in the prophylaxis of spontaneous bacterial peritonitis (SBP) as compared with norfloxacin. Methods: We searched MEDLINE, CINAHL, Google Scholar and Cochrane databases from inception to January 2017. Reference lists of articles as well as conference proceedings were manually screened. We included studies that recruited patients with cirrhosis and ascites who met the criteria for primary or secondary SBP prophylaxis as defined by the European Association for the Study of the Liver and American Association for the Study of Liver Diseases. Two independent investigators reviewed the studies for eligibility, extracted the data and assessed study quality using the Cochrane risk of bias tool. The primary outcome was occurrence of SBP. Secondary outcomes included mortality and adverse events with therapy. Results: Of the 435 studies identified, a total of five were included for full-text review. Four studies were eligible for the systematic review, three of which were randomised controlled trials and one was a prospective observational study. The population examined in majority of studies was primarily hepatitis C cirrhosis. The results of individual studies indicated either superior efficacy of rifaximin or no statistical difference between rifaximin and norfloxacin for SBP prophylaxis. Conclusions: Moderate-quality evidence shows that long-term use of rifaximin appears to be a reasonable alternative to norfloxacin for SBP prevention in hepatitis C cirrhosis.